The social construction of kidnapping: a critical perspective - Tamayo Gomez, Camilo (Routledge studies in crime and society, 2026)
Moving beyond simplistic and sensationalist portrayals of kidnapping, this book offers a critical and interdisciplinary analysis that examines kidnapping as a social, historical, cultural, and political phenomenon. - Kidnapping is a profound violation of human rights that reshapes societies, disrupts governance, and inflicts lasting trauma on individuals and communities. In Colombia, kidnapping became an endemic feature of the armed conflict, leaving tens of thousands of families in a perpetual state of uncertainty and fear. Through an innovative blend of criminology, sociology, transitional justice, surveillance studies, and collective memory epistemologies, this book unpacks kidnapping as a crime of (im)mobility, a strategy of war, and a serious human rights violation. Drawing on fifteen years of research, including statistical analysis, archival work, and interviews with former hostages, ex-combatants, and policymakers, it reveals how kidnapping shaped Colombia's conflict and its ongoing efforts toward justice, truth, and reconciliation. By exploring its patterns, motivations, and legacies, this book not only sheds light on Colombia's experience but also contributes to global discussions on transitional justice, collective memory, and the strategies societies adopt to confront mass victimisation. - "The Social Construction of Kidnapping" is essential reading for scholars and students of criminology, transitional justice, human rights, political violence, and Latin American studies, as well as policymakers, human rights advocates, and anyone seeking a deeper understanding of how societies confront legacies of mass victimisation and forge paths toward accountability and healing.